The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1093/nar/gkt768
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of mitochondrial transcription by mitochondrial topoisomerase I

Abstract: Mitochondrial topoisomerase I is a genetically distinct mitochondria-dedicated enzyme with a crucial but so far unknown role in the homeostasis of mitochondrial DNA metabolism. Here, we present data suggesting a negative regulatory function in mitochondrial transcription or transcript stability. Deficiency or depletion of mitochondrial topoisomerase I increased mitochondrial transcripts, whereas overexpression lowered mitochondrial transcripts, depleted respiratory complexes I, III and IV, decreased cell respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 44 publications
(97 reference statements)
8
46
4
1
Order By: Relevance
“…Mitochondria from mammalian fibroblasts contain a specific DNA topoisomerase, topoisomerase I. Sobek et al (52) report increased transcription of respiratory chain mitochondrial genes when DNA topoisomerase I is either deficient or depleted. It is concluded that topoisomerase I inhibits mitochondrial DNA transcription and that release of transcriptional inhibition is accompanied by increased respiratory rate and superoxide production (52).…”
Section: Experimental Evidence Bearing Directly On Corr Evidence 1: Smentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondria from mammalian fibroblasts contain a specific DNA topoisomerase, topoisomerase I. Sobek et al (52) report increased transcription of respiratory chain mitochondrial genes when DNA topoisomerase I is either deficient or depleted. It is concluded that topoisomerase I inhibits mitochondrial DNA transcription and that release of transcriptional inhibition is accompanied by increased respiratory rate and superoxide production (52).…”
Section: Experimental Evidence Bearing Directly On Corr Evidence 1: Smentioning
confidence: 99%
“…It is concluded that topoisomerase I inhibits mitochondrial DNA transcription and that release of transcriptional inhibition is accompanied by increased respiratory rate and superoxide production (52). DNA topoisomerase is also implicated in redox control of transcription of mitochondrial DNA in plant tissue (53).…”
Section: Experimental Evidence Bearing Directly On Corr Evidence 1: Smentioning
confidence: 99%
“…Some drugs have been reported to deplete mitochondrial DNA by interfering with mitochondrial DNA polymerase gamma activity (Rowe et al, 2001;Neuzil et al, 2013). Top1mt is also important for mitochondrial homeostasis (Douarre et al, 2012), mtDNA replication (Zhang and Pommier, 2008), mtDNA transcription (Sobek et al, 2013), and mtDNA integrity (Medikayala et al, 2011). Yet, there are no drugs known to specifically target Top1mt.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike TOP2Β (Low et al, 2003) and TOP3Α, TOP1mt is the only topoisomerase gene coding for a single polypeptide solely targeted to mitochondria (Zhang et al, 2001;Chinnery and Hudson, 2013). In addition to studying Top1mt's roles in regulating mtDNA replication (Zhang and Pommier, 2008), transcription (Sobek et al, 2013), and mtDNA integrity (Medikayala et al, 2011), it has become possible to examine Top1mt functions genetically. Murine embryonic fibroblasts generated from TOP1mt knockout mice exhibit mitochondrial defects with marked increase in reactive oxygen species production, calcium signaling, hyperpolarization of mitochondrial membranes, and increased mitophagy (Douarre et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The rate-limiting enzyme in catecholamine synthesis, which is TH, indicates a selective increase in TH mRNA (mitochondria ribosomal nuclear atom). This is normally accompanied by a corresponding response in immune reactive TH protein owing to various stressors in the environment (Blanchard et al, 2001;Sobek et al, 2013;Janska & Kwasniak, 2014).…”
Section: Catecholamines Cortisol and Glucocorticoidsmentioning
confidence: 99%